Emerging Characterization Techniques for Electrode Interfaces in Sulfide‐Based All‐Solid‐State Lithium Batteries. Issue 1 (17th November 2021) - Zhao, Feipeng; Zhang, Shumin; Li, Yanguang; Sun, Xueliang
Abstract : All‐solid‐state Li batteries (ASSLBs) are attracting increasing attentions due to their improved safety and high energy density compared with conventional liquid electrolyte‐based Li‐ion batteries (LIBs). ASSLBs based on sulfide solid‐state electrolytes (SEs) is one of the most popular categories, because sulfide SEs have a very competitive ionic conductivity (up to over 10 −2 S cm −1 at room temperature), medium mechanical stiffness, decent contact with electrode materials, and negligible grain boundary resistance. However, interface problems between electrode materials and sulfide SEs seriously plague the development of high‐performance sulfide‐based ASSLBs. In‐depth understandings on the electrode interface problems are pivotal to propose and explore effective strategies to alleviate those issues. In recent years, diverse advanced characterization techniques have been developed, which deepen insights into the problematic interface from physical, chemical, electrochemical, and mechanochemical perspectives. Herein, electrode interfaces and their fundamental knowledge in sulfide‐based ASSLBs are first clarified. Second, various emerging characterizations are overviewed to illustrate the interfacial issues on both oxide cathode/sulfide SE and Li anode/sulfide SE interfaces. Meanwhile, advantages and disadvantages of each characterization techniques are explicated. Finally, an outlook of advanced characterizations that are specifically adapted for interface analysis in sulfide‐based ASSLBs is proposed. Abstract : Deep understandings on the electrode/sulfide interface issues are critical to fabricate high‐performance all‐solid‐state lithium batteries based on sulfide electrolytes. Advances of emerging characterization methods are overviewed herein to provide in‐depth insights into the interface problems. This review is expected to inspire generations of novel interface‐targeted modifications and electrolyte designs.